A poesia nas histórias da literatura goesa de língua portuguesa - Garmes, Helder (Navegações, 2017)
A ex-colônia portuguesa de Goa, na Índia, teve uma significativa e hoje pouco conhecida produção poética em língua portuguesa. Ainda que parcamente estudada, mereceu a atenção de alguns historiadores e críticos. O presente artigo realiza um percurso por esses textos históricos e críticos que procuraram traçar um panorama da poesia goesa de língua portuguesa. Pretende-se reunir neste trabalho as poucas tentativas de se narrar essa história e, assim, sistematizar a historiografia acerca dessa poesia e chegar a delinear um panteão mais preciso desses poetas nos séculos XIX e XX. Busca-se também avaliar sumariamente até que ponto tais tentativas foram bem-sucedidas e que diferentes perspectivas assumiram. Finalmente, nosso intuito é o de sugerir uma nova abordagem para a reescritura dessa história. ******************************************************************** Poetry in the Histories of Goan Literature in Portuguese Abstract: Goa, the former Portuguese colony in India, had a relevant but little known poetical production in the Portuguese language. Still, though little tudied, it has received some attention from historians and critics. In this context, this article aims at tracing the itinerary of these historical and critical texts that bring a panorama of Goan poetry in Portuguese. This paper also analyzes the very few attempts made so far at narrating this poetical history and, consequently, also has as its objective to contribute to the systematization of the historiography on Goan poetry in Portuguese and the creation of a more accurate pantheon of these poets during 19th and 20th Centuries. It is also the aim of this work to briefly appraise to what an extent these attempts have been successful as well as the varied perspectives from which they have been made. Finally, our intention is to suggest a new approach for the rewriting of this literary history. Keywords: Poetry; Goan Literature in Portuguese; Indo-Portuguese Literature; History of Literature.